2021
DOI: 10.3390/su13031043
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Active Luminous Lane Markings on Highway at Night: A Driving Simulation Study

Abstract: Road lane markings play an essential role in maintaining traffic order and improving traffic safety and efficiency. Active luminous lane markings have emerged with advances in technology recently. However, it is still not completely clear what impact their application will have on drivers. This paper aimed to study the effectiveness of active luminous lane markings on highways at night. A driving simulation experiment was carried out based on advanced driving simulators at Tongji University. The driving simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Shang [ 26 , 27 ] proposed a method to set exit advance guide signs in highway tunnels, and evaluated their influence on the trajectories and speeds of passenger cars. Zhu [ 28 ] evaluated the effectiveness of three types of speed reduction markings (SRMs) in tunnel entrance and exit zones through a driving simulation experiment, and found that SRMs are necessarily implemented in the highway tunnel entrance and exit zones. Rain and snow can lead to a bad line of sight, weaken anti-skiing ability, and aggravate risks at tunnel entrances and exits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shang [ 26 , 27 ] proposed a method to set exit advance guide signs in highway tunnels, and evaluated their influence on the trajectories and speeds of passenger cars. Zhu [ 28 ] evaluated the effectiveness of three types of speed reduction markings (SRMs) in tunnel entrance and exit zones through a driving simulation experiment, and found that SRMs are necessarily implemented in the highway tunnel entrance and exit zones. Rain and snow can lead to a bad line of sight, weaken anti-skiing ability, and aggravate risks at tunnel entrances and exits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The number and severity of crashes are significantly higher than during the day because of the lower quantity and quality of available visuals [4]. The low visibility of the night environment and the limited guiding ability of road markings are the main risk factors triggering traffic accidents at night [5,6]. In the United States, the annual number of fatalities has risen by 11% compared to 2010, reaching 38,800 people.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many investigations have been devoted to the search for new application fields for phosphor materials, such as plant growth, 7–11 optical sensors, 12–17 cosmetics 18,19 anti-counterfeiting 20 and road signs/lanes. 21,22 In addition, the phosphors have been used in the dental field to enhance the aesthetics of artificial crowns and restoration. 21–29 Under UV-light irradiation, human natural teeth emit cyan blue color with peak at 450 nm and the photoluminescence (PL) properties of teeth make whiter and brighter for human natural teeth in daylight.…”
Section: Introductionmentioning
confidence: 99%
“… 21,22 In addition, the phosphors have been used in the dental field to enhance the aesthetics of artificial crowns and restoration. 21–29 Under UV-light irradiation, human natural teeth emit cyan blue color with peak at 450 nm and the photoluminescence (PL) properties of teeth make whiter and brighter for human natural teeth in daylight. 30 The artificial crowns and restorative materials can match the shade of the natural teeth to satisfy aesthetic requirements by adding phosphors or pigments.…”
Section: Introductionmentioning
confidence: 99%